Comparative performance analysis of subcarrier assignment for real‐time video traffic. Issue 6 (1st November 2015) - Benita, J.; Jayaparvathy, R.
Abstract : The ability to transmit video and carry real‐time multimedia applications such as video‐streaming, video conferencing and mobile TV are considered important to support the viability and survivability of next generation mobile wireless networks. High peak transmission rate, spectral efficiency and multiple channel bandwidth requirements influence the design of next generation networks. For efficient usage of resources a number of block assignment strategies are followed based on congestion of traffic and priority of the service. Efficient block assignment schemes such as dynamic channel assignment (DCA) and dynamic packet Assignment (DPA) have been analysed in the literature. The authors propose a block assignment strategy for video traffic which sends video bursts over multiple blocks of orthogonal frequency division multiplexed access subcarriers simultaneously considering the interference characteristics of the channel. They present an analytical model using stochastic petrinets and compute the performance of the system in terms of mean delay and normalised system throughput. The results are validated using simulations. They compare the performance of the proposed sub‐sequence DPA scheme in terms of mean delay and normalised throughput with DPA and DCA. It is observed that with the proposed strategy there is an increase in normalised throughput by 66 and 57% and reduction in mean delay by 74 and 61% for DCA and DPA, respectively.